Cool transportation in Nigeria: Intervention, baseline and randomized controlled trial - Yamauchi, Futoshi; Dauda, Bawa; Balana, Bedru; Edeh, Hyacinth O.; Shi, Weilun (International Food Policy Research Institute, 2024)
In many developing countries, including Nigeria, much of fruit and vegetable production is lost largely because of lack of an adequate cold chain, including postharvest handling, cold storage and temperature-controlled transportation. As a result, not only the availability of fish, fruits, vegetables, milk, eggs and meat but also the safety and nutritional content of the food are affected. Under such conditions, all agents in the supply chain including farmers suffer from income reduction, while consumers face un-stable and lower-quality supply of normally more nutritious foods. Inadequate development of value chains and deficiencies in high costs associated with cooling systems are main causes of such losses.